Мотиваційні предиктори спрямованості особистості - Богдан, Жанна Борисівна; Підбуцька, Ніна Вікторівна (Рівненський державний гуманітарний університет, 2017)
Стаття присвячена аналізу особливостей реалізації у професійній діяльності. Розглядається феноменологія поняття "діяльність", "професійна діяльність". Досліджуються особливості прояву професійної мотивації, рівнів розвитку її видів шляхом порівняння респондентів різних видів провідної діяльності. Визначаються мотиваційні предиктори таких видів спрямованості особистості, як професійна, емоційна, інтерактивна. Головними предикторами загальної спрямованості встановлено: загальної спрямованості – внутрішня мотивація, емоційної спрямованості – зовнішня позитивна та негативна мотивація. Узагальнено місце мотиваційних установок у спрямованості особистості.

The details of the professional activity are analyzed in the paper. It is considered phenomenology concept of "activity", "professional activity". We study the features of professional motivation, development levels of its types by comparing different kinds of respondents’ activity. We identify motivational predictors of such individual’s orientation as professional, emotional, interactive. By the main predictors of overall direction it is determined: in the context of overall direction – internal motivation, in the context of emotional orientation – positive and negative external motivation. The place of motivational purposes in the orientation of an individual is generalized. As a result of the empirical research the relationship between motivation and professional orientation of the individual’s orientation was determined. Employees with internal motivation of work are focused on activity, on interaction and have the emotional and communicative orientation. Thus relationship and productive activities are the most important for these employees; they enjoy and look for them. Employees with external positive motivation to work have the focus on personal interests, active and emotional focus. They seek their own benefit, know how to achieve it. Employees of external negative motivation to work have the focus on themselves: marginal, aesthetic and hedonistic. They tend more to enjoy life, they have no inner desire to work, and work is seen as a necessity. So, knowing the motivation type to work of each worker it is possible to manage effectively for improving the productivity and quality of work.
Motyvational predictors of the individual’s orientation
Keywords: мотивація; професійна діяльність; професійна спрямованість; емоційна спрямованість; інтерактивна спрямованість; установки особистості; кореляційний зв'язок; motivation; professional activity; professional orientation; emotional orientation; interactive orientation; personality purposes; correlations